1981
DOI: 10.1097/00006842-198104000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cortisol Response to Incremental Work in Experienced and Naive Subjects

Abstract: Twelve experienced and seven naive male subjects with a similar Vo2max, performed an incremental work test on an electronically braked bicycle until exhaustion. High venous lactate concentrations were recorded in both groups (naive-11.74 +/- 2.43, experienced-13.96 +/- 2.36 mmol/liter). No significant relationship could be demonstrated between Vo2max, venous lactate concentration, Borg ratings of perceived exertion, and the serum cortisol response. The postexercise increase in serum cortisol was significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Both ACTH and cortisol were elevated during first laboratory experience (accommodation), relative to exposure, even though distress was much lower during accommodation. HPA reactivity to novelty, and adaptation with repeated experience, is seen in both healthy and specific phobia participants (Curtis et al, 1976; Davis et al, 1981; Peters et al, 2011). Notably, in this and other data (e.g., Curtis et al, 1976), novelty effects were more striking than HPA responses to the more emotionally distressing fear exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ACTH and cortisol were elevated during first laboratory experience (accommodation), relative to exposure, even though distress was much lower during accommodation. HPA reactivity to novelty, and adaptation with repeated experience, is seen in both healthy and specific phobia participants (Curtis et al, 1976; Davis et al, 1981; Peters et al, 2011). Notably, in this and other data (e.g., Curtis et al, 1976), novelty effects were more striking than HPA responses to the more emotionally distressing fear exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work has confirmed that contextual factors like novelty/familiarity, lack of or access to control or coping responses, and availability of social support are more closely linked to HPA axis activation or moderation than subjective distress per se. For example, novelty robustly activates and familiarity reduces cortisol release in animals (Hennessy et al, 1995) as well as humans (Davis et al, 1981; Peters et al, 2011). Lack of stressor controllability and social evaluative threat are potent and reliable activators of human HPA axis activity (Dickerson and Kemeny, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, physical activity stimulates cortisol release. Davis et al [101] investigated 'exercise to exhaustion' on a laboratory cycling machine. The cortisol levels rose significantly after exercise, with experienced athletes showing a 78% increase in cortisol and normal volunteers demonstrating a 138% increase in cortisol (note: the acute cortisol release may explain why physical activity and sports are inherently pleasurable).…”
Section: Cortisol and The Bioenergetic Stress Model Of Mdmamentioning
confidence: 99%
“…6,14 A "positive outcome expectancy" based on acquired control over a potential threat is the most reliable way to reduce neuroendocrine stress responses. 6 Prior exposure (reduced novelty), 15,16 access to "help" (social support), 17 and past experience suggesting that a challenge can be mastered (control) 18 may all reduce HPA axis activation by enhancing positive outcome expectancies (coping). 6,19 Training in stress management or coping can in fact reduce HPA responses to acute challenge in humans, 20 suggesting that we can perhaps develop specific, teachable techniques to actively ameliorate the detrimental health effects of stress.…”
mentioning
confidence: 99%